Healthline with Paul Douglas - Douglas, Paul; Trinity Healthforce Learning (Carrollton, US : Trinity Healthforce Learning, 1997)
A talkshow program by Paul Douglas that discusses on aging and exercise
Title from title screen
Keywords: Aging -- Physiological aspects; Exercise -- Physiological aspects; Cognition in old age; Health behavior